2015
DOI: 10.3390/met5042372
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Corrosion between Alloy 690 and Magnetite in Alkaline Aqueous Solutions

Abstract: Abstract:The galvanic corrosion behavior of Alloy 690 coupled with magnetite has been investigated in an alkaline solution at 30 °C and 60 °C using a potentiodynamic polarization method and a zero resistance ammeter. The positive current values were recorded in the galvanic couple and the corrosion potential of Alloy 690 was relatively lower. These results indicate that Alloy 690 behaves as the anode of the pair. The galvanic coupling between Alloy 690 and magnetite increased the corrosion rate of Alloy 690. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Therefore, even if trace amount of Cu particles are present in the SG tube deposits, the Cu removal process should be included in the chemical cleaning process. As reported in many previous studies [4][5][6][7][8][9], this work again confirmed that magnetite accelerates the corrosion rate of SG materials by galvanic coupling. In addition, the results in this work had shown that metallic Cu and Pb as well as magnetite increased the corrosion rate of SG materials.…”
Section: Galvanic Coupling Sg Materials Galvanic Corrosion Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, even if trace amount of Cu particles are present in the SG tube deposits, the Cu removal process should be included in the chemical cleaning process. As reported in many previous studies [4][5][6][7][8][9], this work again confirmed that magnetite accelerates the corrosion rate of SG materials by galvanic coupling. In addition, the results in this work had shown that metallic Cu and Pb as well as magnetite increased the corrosion rate of SG materials.…”
Section: Galvanic Coupling Sg Materials Galvanic Corrosion Parameterssupporting
confidence: 90%
“…Recently, many investigations on the galvanic effect by magnetite on the corrosion behavior of secondary coolant system materials such as nickel-based alloys [4][5][6] and carbon steel [7][8][9] have been reported. It is well known that the SG deposits mainly consist of magnetite and are porous in nature [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods for the manufacture of magnetite electrodes have been reported in the literature: casting molten magnetite [15,16], sintering magnetite powder [17,18], sputtering deposition [19], etc. However, a simpler method was recently developed to electrodeposit a magnetite layer onto carbon steel and Ni-based alloy substrates [20][21][22][23], and was verified to be useful for making electrochemical electrodes [4][5][6][7][8][9].…”
Section: Preparation Of Working Electrodes For the Electrochemical Testsmentioning
confidence: 99%
“…It has been reported that a galvanic coupling with magnetite accelerates the corrosion of secondary system materials: carbon steel [4][5][6], alloy 600 [7] and alloy 690 [8,9] in various environments simulating the secondary conditions of SGs. Most of the tubes and heated crevices in operating SGs are covered with deposits or sludge.…”
Section: Introductionmentioning
confidence: 99%